(3TQM gOGjI GdCHgQjs - (3GdMSjfj GdnerjnHPj, bGVj ejQ, MSjf Hf eYjf GdOjf, J (B910 (3g`s ((3eOQSI NSQh HGTG HeOjfI BeOs)
(3ChdgG (B:s
(3HSe Gddg deG QCjJ ceGd Yjf GdCYjGf hgh fhY GdEfSGf HGdGQJbGA Edi CYdGe GdaWfI hGdGgJOGA Edi CbSGe GdMceI EP HgG jUjQ GdfGXQ aj MbGFb GdCTjGA HUjQG hefg jDJi GdMceI s
(3BNQgG (B:s
(3hbjd fRdJ Edi GdCLSGe GdfHGJjI hjSei QSNG hbjd Edi GdLeGOjI cGdeYGOf hGdHSGjW hjeSi aSNG hbO jbGd gj JJYdb HHYV GdCLQGe GdSeGhjI ddGSJceGd hef CQGO GdGSJbUGA aj GdMceI Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 260s
(3cTa GdXfhf (B2 / 2029s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs